(untitled) (Applied Biological Research, 2017)
The gga-miR-142-3p is highly expressed during immune organ development and functional stages in chicken embryo. The present study was carried out to explore the role of miR-142-3p and its importance in regulating the expression of target gene CD200 involved in signal transduction and immune response. Presence of binding site for miR-142-3p on 3’ UTR of CD200 gene was identified by bioinformatics analysis. Real time qPCR analysis revealed significant changes in the expression of CD200 gene in immune organs and other organs of miRNA knockdown embryos compared to scramble control embryos. Altogether, knockdown of gga-miR-142-3p in the chicken embryo resulted in the over expression of CD200 in immune organs and visceral organs indicating CD200 as a validate target of gga-miR-142-3p. This study suggests aberrant expression of gga-miR-142-3p during the embryonic developmental stage may lead to malfunctioning of the immune organs.